2021
DOI: 10.3390/cancers13133249
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between Patients’ Clinicopathological Characteristics and Their Association with Response to Immunotherapy in a Real-World Cohort of NSCLC Patients

Abstract: Immune checkpoint inhibitors (ICIs) have transformed non-small cell lung cancer (NSCLC) treatment. Unfortunately, only some patients benefit from these therapies. Thus, certain clinicopathological characteristics of the patients have been proposed as biomarkers of ICIs response. We assembled a retrospective cohort of 262 NSCLC patients treated with ICIs, compiled relevant clinicopathological characteristics, and studied their associations with treatment outcome using Cox proportional-hazards survival models. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“… 33 In a recent study analyzing clinicopathological features, female sex—among other characteristics—was associated with increased PFS following ICIs treatment in NSCLC. 34 …”
Section: Discussionmentioning
confidence: 99%
“… 33 In a recent study analyzing clinicopathological features, female sex—among other characteristics—was associated with increased PFS following ICIs treatment in NSCLC. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Based on our in-house cohort, we found that the use of statin was remarkably related to improved clinical outcome in NSCLC patients. Although multiple studies have uncovered the combination of statin with PD-1 inhibitors in various cancers (44)(45)(46)(47)(48)(49), these clinical studies had too few patients receiving statin to evaluate potential confounding effects. Therefore, we conducted a meta-analysis to assess the effect of statin use on anti-PD-1 immunotherapy, and we observed a potential indication that the use of statin may improve OS in the NSCLC patients receiving immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… Other clinical factors: The best association for any response to immunotherapy was found with the combination of LDH levels, TRAEs, and sex. Thus several clinicopathological features may be utilized as biomarkers in the real world 155. Several other relevant clinical factors, including poor performance status due to cancer-related conditions, metastasis, concomitant therapies, and radiologic features have been related to a reduced clinical benefit from ICI 156–158…”
Section: Biomarkersmentioning
confidence: 99%